EFFECT OF ULTRAVIOLET RADIATION ON THE LYMPHOID SERIES OF THE HEMOPOETIC SYSTEM OF GUINEA PIG (CAVUS PORCELLUS) - ARCHANA PRASAD; SOMA ROY; VANDANA KUMARI (The Bioscan, 2012)
Guinea pigs (C. porcellus) were exposed to UV radiation for different durations and hematological parameters have been observed after exposure. The observation gives a clear indication that intermittent exposure (15min, 30min, 1h) of mild doses of UV radiation shows immune response in terms of increased leucocytic count specially lymphocytes and neutrophil.